СОСОТОЯНИЕ И ПЕРСПЕКТИВЫ МНОГОСТОРОННЕГО ЭКОНОМИЧЕСКОГО СОТРУДНИЧЕСТВА КАЗАХСТАНА И РОССИИ: STATE AND PROSPECTS OF MULTILATERAL COOPERATION BETWEEN KAZAKHSTAN AND RUSSIA - Нурлихина Гульмира, Нурлихина Гульмира; Мекин Мәдениет, Мекин Мәдениет; Серикбаев Серик, Серикбаев Серик; Кулбай Бауыржан, Кулбай Бауыржан; Исагалиев Сакен, Исагалиев Сакен (Scientific Journal of Pedagogy and Economics, 2024)
The article is devoted to the problems of foreign economic cooperation between Kazakhstan and Russia. The study used descriptive-inductive analysis, a systematic approach, sampling of necessary information, logical inferences and a comparative method. Indicators of global competitiveness of states are considered. It is concluded that through cooperation between countries it is possible to achieve significant GDP growth, technological independence, and strengthen Eurasian economic integration. An analysis of the foreign trade turnover of Russia and Kazakhstan has been carried out, and although 76 out of 85 constituent entities of the Russian Federation have trade relations with Kazakhstan, trade relations need to be expanded. It is indicated that the raw material nature of trade between countries creates problems in foreign trade. It has been established that to expand trade it is necessary to eliminate currency disparity and remove non-tariff restrictions. That is why the purpose of the research is to consider multilateral mechanisms of Russian-Kazakh foreign economic cooperation, to search for effective and scientifically supported programs. proposals for the development of cross-border trade and economic cooperation between Russian regions and neighboring regions of Kazakhstan.The expediency of joint efforts within the EAEU is noted, which helps to eliminate obstacles that impede the deepening of integration processes.